The Effectiveness of Android-Based Learning Media on Science Lesson Content to Increase Motivation and Digital Literacy of Grade V Elementary School Students (Universitas Negeri Semarang, 2022)
Information and communication technology has become an important role in education, one of which is Android. Android-based application development in the form of Android-based learning media with science content. The goal of this study is to examine the effectiveness of Android-based learning media in science lesson content in terms of increasing students' motivation and digital literacy. The participants in this study were fifth-grade students in Mijen District, Semarang, during the even semester of the 2021/2022 academic year. This study's sample consists of fifth-grade students from SDN Polaman as the experimental group and fifth-grade students from SDN Karangmalang as the control group. Questionnaires and exams of students' digital literacy skills were used to collect data. To determine the increase in students' learning motivation and digital literacy, the data analysis technique included descriptive analysis, completeness test, paired test, N-gain, and independent t-test. The findings revealed that 1) students' learning motivation was indicated by an average score of 84.58 percent in the post-learning experimental class, which was classified as very high, 2) The descriptive test on the pretest received a score of 74.00 and the posttest received a score of 90.40, 3) the test completeness resulted in 92 percent completion, and 4) the improvement test resulted in a sign. two-tailed value of 0.000 indicates that Ha was accepted or that there was a significant difference, 5) The average N-Gain in the experimental class was 0.66, which was in the medium group, while in the control class was 0.142 categorized as low. 6) The comparative test yielded a positive result with a sign. 2-tailed score of 0.000 or Ha was accepted, indicating that the average posttest score differed. According to the above-mentioned test results, Android-based learning media in scientific lesson content is effective for enhancing students' motivation and digital literacy